The role of Islamic leadership as a determinant of employee behavior and work behavior in improving innovative work - Dina Novita (Jurnal Sinar Edukasi, 2024)
This study examines the role of Islamic leadership as a determinant of employee behavior, work behavior, and innovative work through a Systematic Literature Review (SLR). Articles published in peer-reviewed journals over the last ten years were systematically selected and analyzed. The findings indicate that Islamic leadership, grounded in ethical and spiritual values, positively influences employee motivation, collaborative work behavior, and innovative work outcomes. Islamic leadership fosters a supportive and value-driven work environment that enhances psychological well-being and encourages sustained innovation. These findings highlight the relevance of Islamic leadership as an effective leadership model in contemporary organizations.